The Role of Family and Workplace Support in Sustaining Exclusive Breastfeeding Among Working Mothers: A Scoping Review - Fitriani, Desiy; Sartika, Maya; Sayekti, Wahyu Nindi (Utan Kayu Publishing, 2024)
The composition of breast milk is the best way to provide the nutrients a baby needs for healthy growth and development. Maternal employment also plays a role in the decline in breastfeeding rates. Providing breast milk or breastfeeding is a behavior that can be taught by the family to the mother by providing family support, especially husband support. Research objective: to review literature discussing family support for working mothers in providing exclusive breastfeeding. Method: Preparation of a scoping review using the framework from Arksey and O'Malley. Results: Based on 6 selected articles, 3 with cross-sectional design, 1 descriptive study, 1 quantitative and qualitative data, and 1 qualitative data. The results of the research obtained three themes, namely factors that influence the success of providing exclusive breastfeeding, forms of support and obstacles experienced in providing exclusive breastfeeding. Conclusion: Family support, including husband's support, is one of the factors associated with exclusive breastfeeding. It was found that lack of support from the workplace was an obstacle to breastfeeding. Abstrak: Komposisi ASI merupakan cara terbaik untuk menyediakan nutrisi yang dibutuhkan bayi agar tumbuh kembangnya sehat. Pekerjaan ibu turut memberikan peran pada turunnya angka pemberian ASI . Memberikan ASI atau menyusui merupakan perilaku yang dapat diajarkan oleh keluarga kepada ibu dengan memberikan dukungan keluarga terumata dukungan suami. Tujuan Penelitian: mereview literature yang membahas tentang dukungan keluarga terhadap ibu bekerja dalam memberikan ASI eksklusif. Metode: Penyusunan scoping review menggunakan framework dari Arksey dan O'Malley. Hasil: Berdasarkan 6 artikel terseleksi 3 dengan desain cross-sectional, 1 Studi deskriptif, 1 Data kuantitatif dan kualitatif, dan 1 Data Kualitatif. Hasil penelitian mendapatkan tiga tema yaitu faktor yang mempengaruhi keberhasilan pemberian ASI Eksklusif, bentuk dukungan dan hambatan yang dialami dalam pemberian ASI Eksklusif. Simpulan: Dukungan keluarga termasuk dukungan suami adalah salah satu faktor yang terkait dengan pemberian ASI secara EKsklusif. Ditemukan bahwa kurangnya dukungan dari tempat kerja menjadi penghambat dalam pemberian ASI.